Konflik Hukum Negara dan Hukum Adat dalam Pengelolaan Sumber Daya Alam di Papua Barat Daya - Adirandi M Rajab; Muh Akbar Yanlua (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Southwest Papua is a region rich in natural resources, such as forests, seas, and minerals. For indigenous communities, these resources are not merely economic commodities but also part of their social and spiritual identity. In practice, the state often grants management permits to companies without considering the customary rights of indigenous communities. This situation not only demonstrates the weak implementation of the norms in the 1945 Constitution but also reveals an imbalance in the power relations between the state, corporations, and indigenous communities. When business permits are granted without thorough verification of the existence of indigenous territories, the state indirectly negates the collective rights of indigenous communities. In many cases, areas traditionally managed by indigenous communities are categorized as state land, thus opening up legal space for granting concessions to third parties. As a result, indigenous communities lose control over their own living space, both economically, socially, and culturally. This practice also demonstrates the state's tendency to prioritize an investment-based development approach over protecting indigenous peoples' rights. A development paradigm oriented toward economic growth often positions land and natural resources as commodities, rather than as part of the identity and survival of indigenous communities. This creates a tension between development interests and social justice.